Literasi Lingkungan melalui Pendidikan di MTs Muhammadiyah Gantung Belitung Timur, Bangka Belitung - Gatot Supangkat Samidjo; Aris Slamet Widodo; Linda Kusumastuti; Asyraf Suryadin (Warta LPM, 2023)
The level and amount of environmental degradation has increased, along with the increase in population. Environmental problems that arise are not technical-technological problems, but rather a human behavior. Education is the only way to improve human behavior.  Environmental education needs to be introduced and developed in the society, especially through MTsM Gantung which has adequate educational equipment (infrastructure) (Mangrove Literacy House) and a good education history. However, both hardware and software need to be integrated in an integrated manner to be more effective and efficient.   The problem is, not all educational institutions specifically make environmental education an important subject in the learning process, so environmental education is needed as an effort to literacy and inculcate environmentally friendly behavior.  The method used in this Community Partnership Program (CPP) is Direct Action and Together Learning. Several management techniques were applied, including Participatory Rural Appraisal and Focus Group Discussion. This program was conducted from March to August 2022.  The program results showed that Environmental Education is a new knowledge that has never been known before. Environmental Literacy through education has well understood by teachers and students. The implementation of environmental education is agreed to be included in the curricular learning curriculum as local content, co-curricular as a support for natural science subjects, especially Biology, and extra-curricular as additional knowledge/competence for students. Environmental Education Infrastructure that could use as learning aids for Environmental Education, namely Mangrove Literacy Houses, Mangrove Rehabilitation Areas, Mining Areas, and natural science learning aids that already exist in schools.